PENGARUH MAEKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PADA FERRY JAYA MOTOR LAMONGAN - Nawari Nawari (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2018)
The development of a company result in increasingly tight competition. To be able to face the competition, the company must have an efficient marketing strategy to offer its products to consumers. One such strategy is a marketing mix consisting of product, price, promotion and place. The strategy is also used by Ferry Jaya Motor Lamongan that is able to influence the purchasing decision of motor in lamongan area and its surroundings. Looking at the above phenomenon researchers interested in doing research on the influence of marketing mix variables on purchasing decisions on Ferry Jaya Motor Lamongan. The purpose of this research is to know the role of marketing mix that is Product, Price, Promotion, distribution to purchasing decision at Ferry Jaya Motor Lamongan. This research uses multiple regression analysis and hypothesis test (T and F test) with Likert scale. The sample used is 85 respondents. Based on incidental sampling technique method. the sampling technique by chance, ie anyone who met with researchers at the time that researchers have taken that is in October 2017 until february 2018. The test results simultaneously show product variables, price, promotion and distribution together have a significant effect on the decision purchase at Ferry Jaya Motor Lamongan with Fhitung equal to 92,877> 2,49. While the test partially shows product variables (X1) of 2.570, the price (X2) of 1.796, promotion (X3) of 2.967 and the distribution (X4) of 4.624 significant effect on purchasing decision Y. And variable distribution (X4) purchase decision on Ferry Jaya Motor Lamongan